2019
DOI: 10.1002/jbm4.10236
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Differences in Hip Fracture Mortality: A Nationwide NOREPOS Study

Abstract: Higher hip fracture incidence in urban than in rural areas has been demonstrated, but urban–rural differences in posthip fracture mortality have been less investigated, and the results are disparate. Hence, the aims of the present register‐based cohort study were to examine possible urban–rural differences in short‐ and long‐term mortality in Norwegian hip fracture patients and their potential associations with sociodemographic variables, and to investigate possible urban–rural differences in excess mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
9
1
3
Order By: Relevance
“…In Latin America, the hip fracture rates are similar to the values reported in North America [ 4 ], while urban–rural differences in hip fracture prevalence are well documented, with higher rates in urban areas [ 7 ]. However, urban–rural differences in hip fracture mortality are more confusing, with some studies showing no increase [ 8 ], others finding higher mortality in rural areas [ 9 , 10 ], and others finding higher mortality in urban areas [ 11 ]. Several explanations have been proposed for these contradictory findings: differences in general health in urban–rural populations, including multimorbidity, could be an important reason [ 12 ], and other factors, such as demographics and socioeconomic, social, and environmental factors, could contribute to this difference [ 11 , 13 ], as well as inequalities between urban and rural municipalities regarding follow-up health care services or rehabilitation services [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, the hip fracture rates are similar to the values reported in North America [ 4 ], while urban–rural differences in hip fracture prevalence are well documented, with higher rates in urban areas [ 7 ]. However, urban–rural differences in hip fracture mortality are more confusing, with some studies showing no increase [ 8 ], others finding higher mortality in rural areas [ 9 , 10 ], and others finding higher mortality in urban areas [ 11 ]. Several explanations have been proposed for these contradictory findings: differences in general health in urban–rural populations, including multimorbidity, could be an important reason [ 12 ], and other factors, such as demographics and socioeconomic, social, and environmental factors, could contribute to this difference [ 11 , 13 ], as well as inequalities between urban and rural municipalities regarding follow-up health care services or rehabilitation services [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a Norwegian nationwide study found an increasing degree of urbanization was associated with higher post-fracture mortality, especially the first 1 to 2 years post-fracture [38], which might reflect a higher level of fragility in urban residents. Another Norwegian study demonstrated that urban women had lower BMD, lower BMI, and a higher proportion of poor or fair self-reported health than rural women [39].…”
Section: Plos Onementioning
confidence: 73%
“…Több cikk említi tényezőként a betegnek a sérülés előtti lakóhelyét is. Ezek elsősorban a saját otthonukban és a szociális ellátóintézményekben lakó betegek csoportjait különböztetik meg [24,29,30], de említésre kerül a városi és a vidéki ellátás különbsége is [24,30]. A dementia több közlemény szerint hátrányosan befolyásolja a rehabilitációra kerülést [23][24][25], hiszen hatással van az együttműködési képességre, bár a gyógytorna a demens betegekre is kedvezően hat [31].…”
Section: Eredeti Közleményunclassified
“…A rehabilitációra kerülést vagy a rehabilitáció kimenetelét befolyásoló társbetegségek közül kiemelendők a szív-ér rendszeri betegségek (például korábbi szívinfarktus, coronariasztent), a magas vérnyomás, a diabetes, a krónikus obstruktív tüdőbetegség (COPD), az akut ellátás során beadott transzfúzió, valamint a beteg kognitív állapotára utaló diagnózisok [17,[25][26][27]32]. A beteg lakóhelye a beteg önállóságáról, szociális helyzetéről és az ellátáshoz való hozzáférésről is képet adhat [30].…”
Section: Eredeti Közleményunclassified
See 1 more Smart Citation